Susceptibility to SARS coronavirus S protein-driven infection correlates with expression of angiotensin converting enzyme 2 and infection can be blocked by soluble receptor - Hofmann, Heike (Biochem Biophys Res Commun, 2004)
The angiotensin converting enzyme 2 (ACE2) has been identified as a receptor for the severe acute respiratory syndrome associated coronavirus (SARS-CoV). Here we show that ACE2 expression on cell lines correlates with susceptibility to SARS-CoV S-driven infection, suggesting that ACE2 is a major receptor for SARS-CoV. The soluble ectodomain of ACE2 specifically abrogated S-mediated infection and might therefore be exploited for the generation of inhibitors. Deletion of a major portion of the cytoplasmic domain of ACE2 had no effect on S-driven infection, indicating that this domain is not important for receptor function. Our results point to a central role of ACE2 in SARS-CoV infection and suggest a minor contribution of the cytoplasmic domain to receptor function.